Tourist shopping behavior : a case of Shanghai outbound tourists / Yingzhi Guo...[et al.] - Guo, Yingzhi; Pei, Yanlin; Ye, Yunxia; Chen, Yong; Wang, Kuo-Ching; Chan, Hsi-Chen (Faculty of Hotel Management and Tourism, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2009)
Shopping is an important tourist activity and its contribution to the economy is significant. For many visitors no trip is complete without having spent time shopping and tourists often feel they cannot return home without buying “something”. This research explored the basic shopping behaviour model of Shanghai outbound tourists. Data from 65 respondents were collected using the convenient sampling method. The motivations of Shanghai outbound tourists’ shopping behaviour were presented in seven dimensions including function, gift giving, affection, curiosity, scarcity, memory and cultural orientations. Quality, brand, shortage of specific goods in China’s domestic market, the lower price of goods in the outbound market and the convenient payments in the destinations are important attributes that spark their shopping behaviours. This outcome has at least had significant implications for tour operators and marketers to understand the needs of Chinese outbound tourists.